ANALISIS IMPLEMENTASI PEMASARAN JASA PADA HOTEL ASEAN PEKANBARU - Normayanti, Rida; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to know the implementation services as well as marketing mix factors restricting implementation support and service marketing mixon the Asean Hotel Pekanbaru. The population in this research is a guest staying at the Hotel Asean Pekanbaru in 2015 which reached 9.084. Sampling uses the Slovinâ€™s formula so that it brings as many as 100 people sample respondents. This research analyzes the data by using a descriptive method. The respondents. This research concluded that the implementation of the marketing mix services Hotel Asean Pekanbaru implemented already. However there are still deficiencies in the variable product which do not comply with the standard room 2-star, variable prices is prices offered more expensive when compared to competitors, namely promotion of variable information about hotels that are hard to come by for the people that are outside of the city, the location variable parking is inadequate, the variable that employees who sometimes speak the word irreverent and less friendly to guests and the variable physical evidence that comfort and dÃ©cor of the room the hotel was not good.Key Words : Product, Price, Promotion, Place, People, Process, Physical evidence